Teaching the Classification of Living Things Through Music: Development of Song-Based Video Clip Learning Media - Khairani, Khairani; Sarkity, Dios; Hindrasti, Nur Eka Kusuma (Universitas Islam Riau (UIR) Press, 2026)
This research aimed to develop song-based video clip learning media to support the teaching of the classification of living things for seventh-grade students. The study was conducted at SMP Negeri 11 Tanjungpinang, Riau Islands Province, during the 2024/2025 academic year and involved 30 Grade VII students. The research used a Research and Development (R&D) approach employing the 4D model, which consists of four stages: define, design, develop, and disseminate. Data were collected through interviews, questionnaires, and learning outcome tests. The validation results showed that the material aspect obtained a score of 91%, categorized as very valid. The media aspect reached 79%, and the music aspect obtained 90%, both of which were also classified as very valid. The practicality test indicated that the teacher response reached 88%, while the students’ responses reached 96%, demonstrating that the developed learning media are very practical for use in classroom learning. The effectiveness test using the N-Gain analysis produced a score of 0.77, which is included in the high category. In addition, students’ interest in the use of the learning media reached 92%, indicating a very high level of interest. These findings show that the song-based video clip learning media developed in this study are valid, practical, and effective for supporting science learning on the topic of the classification of living things at the junior high school level.